Law, Christianity and modernism in Islamic society : proceedings of the eighteenth congress of the Union Européenne des Arabisants et Islamisants held at the Katholieke Universiteit Leuven ( September 3 - September 9, 1996 ) (Leuven)
xviii, 299s.